METODE-METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA INDUSTRI 4.0 DALAM PERSPEKIF AL-QUR'AN - Muhammad Iqbal Yuriza; Lukmanul Hakim (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
The term Industry 4.0 was first used at the 2011 Hannover Fair from April 4-8. The term is used by the German government to take the industrial sector to the next level with the help of technology. Quoting the Forbes page, the fourth generation industrial revolution can be interpreted as the intervention of industrial intelligence and automation systems. It is data-driven through machine learning and artificial intelligence (AI) technologies. The Industrial Revolution 4.0 is based on the Internet as the main pillar, combining the online world with the industrial assembly line to realize the transformation of industrial improvement. Its relationship is in the world of Islamic education, so inevitably the digitalization of Islamic education becomes a mandatory domain in its development according to the words of Ali bin Abi Talib